ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT PADA DEALER TOYOTA ASRI MOTOR PUCANG DI SURABAYA - Jhohana A. W. (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Asri Motor is a trading company specializing in the sale of Toyota brand cars. Over time, Asri Motor has been designated as an official "Authorized Toyota Dealer" by PT. Toyota-Astra Motor. The purpose of this research is to determine whether the credit sales accounting information system employed at Asri Motor - Pucang adheres to established accounting theories. The research method employed is a descriptive qualitative approach, with data collection conducted through interviews, observations, and direct documentation. The findings indicate that the information system at Asri Motor aligns with applicable principles, adheres to standards, and demonstrates the effectiveness of separating administrative functions, thereby preventing excessive workloads. Consequently, the implemented system proves advantageous for the company by generating continuous profits.